Effects of arabinoxylan and chlorogenic acid on the intestinal microbiota in dextran sulfate sodium–treated mice - Xie, Minhao; Zhang, Xianzhu; Wang, Xiaoxiao; Chen, Guijie; Liu, Jianhui; Zeng, Xiaoxiong; Yang, Wenjian (Frontiers in Nutrition, 2022)
Dietary non-starch polysaccharides and phenolics are usually ingested at the same time. They are both regarded as prebiotics, and regulate intestinal microbiota through various mechanisms. Notably, the combined or synergistic effects of them were rarely reported. Arabinoxylan (AX) and chlorogenic acid (CA) are widely consumed dietary polysaccharide and polyphenol, respectively, and their effects on microbiota have been reported. In the present study, they were given to dextran sulphate sodium (DSS)-treated mice respectively and together, and the intestinal microbiota were investigated by high throughput sequencing. The data showed that CA attenuated the body weight loss, colon shortening and histological damage in DSS-treated mice, and AX and the combination of AX+CA did not exhibit the ameliorating potential. AX+CA had less modulating effect on the profile of intestinal microbiota than CA. AX+CA administration increased the relative abundance of Flavonifractor, Coprobacillus, and Clostridium_XlVa, and decreased Robinsoniella, and Lactobacillus populations in mice drinking DSS solution. Compared to AX and CA, AX+CA contributed to more complicated shift in the biological functions of intestinal microbiota. It seemed that AX weakened the benefit effects of CA at least in the present DSS-induced experimental colitis model. The combined effects and mechanisms of dietary polysaccharides and phenolic compounds on intestinal microbiota and health still need to be investigated in further.